Producing self tuned music using machine learning tools - Tasneem, Akifa; Reza, Mostofa Saif; Anindya, Navid (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.